Gênero e sexualidade em educação: um mapeamento das teses e dissertações do Norte e Nordeste brasileiro - Santos, Linda Brasil Azevedo (2020)
Education has a fundamental role in the (de)construction of prejudice and stereotypes that affect LGBTQI + peoples. In view of this, there is increasing number of scientific researches addressing gender and sexual diversity. This dissertation is a "State of the Art" study, with the objective of analyzing scientific research in education on sex and sexuality carried out by postgraduate programs in higher education institutions in the North and Northeast regions of Brazil. For this, we mapped theses and dissertations from 1994 to 2018 through a quantitative and qualitative approach. The Brazilian Digital Theses and Dissertations platform - BDTD, was the chosen database and the search was conducted with the following descriptors: gender, sexuality and education. A total of 403 papers, 301 dissertations and 102 theses were selected, which discussed educational processes in schools and universities, as well as analytical papers on education national policies. We also looked into the authors’ gender, theoretical background and institutional afilliation. From these, we selected 107 surveys carried out in the North and Northeast, taking a qualitative approach, categorizing them by curricula, teacher training, pedagogical practices and resulting experiences.